The Impact of Oil Price Shocks on Economic Growth: The Case of Taiwan - Chen, Kuan-Chieh (International Journal of Economics and Financial Issues, 2021)
Most studies continue to analyze oil shocks. Earlier authors recognize that oil price volatility plays a critical role in the economy. There is accordingly evidence that oil price shocks negatively impact real gross domestic product (GDP) growth rates and cause higher inflation. However, this paper uses different perspectives to investigate whether it is beneficial to Taiwan’s overall economy based on a low oil price event. This study’s results reveal that an increase in the oil price leads to an increase in the consumer price index (CPI), causing higher inflation. Moreover, a long-term rise in oil prices would negatively impact the GDP growth rate. Alternatively, in the event of falling oil prices, there may not be an immediate decline in the price of goods. However, firms’ reductions in the cost of goods resulted in declining CPI, due to the decreasing oil price over the past few months. Furthermore, it was observed that GDP would decrease when there is a long-term decline in the oil price. All the previously mentioned results are almost consistent with those of previous studies of high oil price events. In addition, the economy would be negatively impacted by a long-term decline in oil prices. Keywords: Oil price shocks, Oil fluctuation, Economic activity, Impulse response function JEL Classifications: F62, M21, O11, Q43 DOI: https://doi.org/10.32479/ijefi.11822